Interventional radiology versus operative management for splenic injuries: a study protocol for a systematic review and meta-analysis - Kazuma Yamakawa; Masahiro Kashiura; Noritaka Yada (BMJ Open)
Introduction Over the past decades, the treatment for blunt splenic injuries has shifted from operative to non-operative management. Interventional radiology such as splenic arterial embolisation generally increases the success rate of non-operative management. However, the type of intervention, such as the first definitive treatment for haemostasis (interventional radiology or surgery) in blunt splenic injuries is unclear. Therefore, we aim to clarify whether interventional radiology improves mortality in patients with blunt splenic trauma compared with operative management by conducting a systematic review and meta-analysis.Methods and analysis We will search the following electronic bibliographic databases to retrieve relevant articles for the literature review: Medline, Embase and the Cochrane Central Register of Controlled Trials. We will include controlled trials and observational studies published until September 2018. We will screen search results, assess the study population, extract data and assess the risk of bias. Two review authors will extract data independently, and discrepancies will be identified and resolved through a discussion with a third author where necessary. Data from eligible studies will be pooled using a random-effects meta-analysis. Statistical heterogeneity will be assessed by using the Mantel-Haenszel χ² test and the I² statistic, and any observed heterogeneity will be quantified using the I² statistic. We will conduct sensitivity analyses according to several factors relevant for the heterogeneity.Ethics and dissemination Our study does not require ethical approval as it is based on the findings of previously published articles. This systematic review will provide guidance on selecting a method for haemostasis of splenic injuries and may also identify knowledge gaps that could direct further research in the field. Results will be disseminated through publication in a peer-reviewed journal and presentations at relevant conferences.PROSPERO registration number CRD42018108304.